2018
DOI: 10.1080/2162402x.2018.1466771
|View full text |Cite
|
Sign up to set email alerts
|

Targeting phosphorylated p53 to elicit tumor-reactive T helper responses against head and neck squamous cell carcinoma

Abstract: The human T cell receptor is capable of distinguishing between normal and post-translationally modified peptides. Because aberrant phosphorylation of cellular proteins is a hallmark of malignant transformation, the expression of the phosphorylated epitope could be an ideal antigen to combat cancer without damaging normal tissues. p53 activates transcription factors to suppress tumors by upregulating growth arrest and apoptosis-related genes. In response to DNA damage, p53 is phosphorylated at multiple sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Using bioinformatics analysis of the Cancer Genome Atlas (TCGA) data, we also observed many cytokines and chemokines deregulated in HNSCC (Figure 2). Consistent with these observations, previous studies have also reported a decrease in Th1 and increase in Th2 cytokine levels [117,118] such as IL-4, IL-6, IL-8, IL-10, GM-CSF, VEGF, prostaglandin E2 (PGE2), and bFGF during the development and progression of HNSCC [119][120][121]. While the increased IL-10, IL-17A, and IL-22 levels, and decreased IFN-γ expressions are collaborated with the loco-regional metastasis [122,123], increased VEGF, FGF, and IL-8 expression contribute to tumorigenesis, metastasis, and HNSCC angiogenesis [16,124,125].…”
Section: Deregulated Chemokine and Cytokine Expression In Hnsccsupporting
confidence: 88%
“…Using bioinformatics analysis of the Cancer Genome Atlas (TCGA) data, we also observed many cytokines and chemokines deregulated in HNSCC (Figure 2). Consistent with these observations, previous studies have also reported a decrease in Th1 and increase in Th2 cytokine levels [117,118] such as IL-4, IL-6, IL-8, IL-10, GM-CSF, VEGF, prostaglandin E2 (PGE2), and bFGF during the development and progression of HNSCC [119][120][121]. While the increased IL-10, IL-17A, and IL-22 levels, and decreased IFN-γ expressions are collaborated with the loco-regional metastasis [122,123], increased VEGF, FGF, and IL-8 expression contribute to tumorigenesis, metastasis, and HNSCC angiogenesis [16,124,125].…”
Section: Deregulated Chemokine and Cytokine Expression In Hnsccsupporting
confidence: 88%
“…The expression of apoptins in the downstream of PI3K/Akt signaling pathway was explored, and the results showed that the expression of Caspase-3 and Caspase-9 in the combinational treatment group were remarkably upregulated while the expression of Bcl-2 was markedly downregulated (Figure 6D). Some reports have shown an increase in phosphorylated p53 was induced by treatment with chemotherapeutic reagents in vitro and in murine xenograft models (Ohara et al, 2018). In our present study, there is no change in the expression level of p53 among the different groups, but its phosphorylated expression have been changed after C49 treatment in MCF-7/DOX cells (Figure 6D).…”
Section: C49 Enhanced the Cytotoxicity Of Doxorubicin To Repress Cell Proliferation And Induced Cell Apoptosissupporting
confidence: 43%
“…In addition, the identification of hotspot mutation-derived neo-antigens and their application for tailored neo-antigen therapy has become reality (28). Regarding antigens derived from cancer-specific aberrant post-translational modifications, protein phosphorylation can alter the structure of self-peptides to generate tumor-specific epitopes (29)(30)(31). The functional relevance and efficient detection of these reproducible neo-antigens are under investigation.…”
Section: Neo-antigensmentioning
confidence: 99%